#TITLE_ALTERNATIVE# - ELVINA NOOR (NIM : 12910011); Pembimbing: Dr.rer.nat Mutiara Rachmat Putri, S.Si, M.Si; Mukt, GRIES
Upwellling in the eastern Indian Ocean not only affect the SST, but also stability of water masses. In the stable condition, water density increases toward depth which shows well stratified water masses. However, if the water density decreases toward depth the stratification will be weakened and the vertical mixing such as upwelling will occur easily. Upwelling identification and analysis in the eastern Indian Ocean was doing based on the stability of water masses-which is calculating by Brunt-V is l Frequency (BVF). The data were obtained from CTD measurements of RAMA buoy in 99,99oE-7,89oS which is property of Institute for Marine Research and Observation (BPOL). The data consist of conductivity, salinity, and temperature of seawater between 2 and 100 m from April until October 2012 every 10 minutes. The results ofthis study indicate that upwelling in the eastern Indian Ocean 2012 occurred slowly than normal from mid July to September due to influence of IOD(+) that has a different pattern in 2012. In the mid July, BVF minimum is -9,25x10-6 s-1 at 25-35 m and followed by lifting of isopicknal layer (22kg/m3) from 100m to 70m by vertical current (w) that indicated as generating of upwelling. When upwelling occurs, mixed layer will be depleted from 56,45 m (July) to 53,21 m (September) and BVF relative increased to 1,2 x 10-4s-1 at the end of August. When upwelling and IOD(+) decayed in October, the stability of water masses is reduced to minimum BVF -1,33x10-5s-1.